Overweight and obesity in young adults: relevance of job-related changes of exercise on fat, lean body and body mass in students - Kemmler, Wolfgang; Kohl, Matthias; Bebenek, Michael; von Stengel, Simon (Wiener Medizinische Wochenschrift, 2015)
Early adulthood is related to changes in lifestyle that negatively affect body weight and health. The aim of the study was to determine the effect of exercise changes on the development of weight and body composition in college students.Sixty-one randomly selected dental (ZMS) and 53 sport students (SLS) were accompanied over 5 years. Body mass, fat and lean body mass (LBM) were determined via DXA-technique. Exercise and physical activity were assessed by questionnaires and interviews.All exercise indices significantly increased in the SLS and significantly decreased in the ZMS. Physical activity slightly increased in both groups. Both cohorts comparably gained body mass, however, the increase in the SLS group can be attributed to LBM-changes with minor changes of fat-mass (2.4 % ± 3.3 % vs. 0.1 ± 1.0 %) whereas ZMS gained fat and LBM in a proportion of 2:1.Maintenance/increase of exercise compensate the negative effects of lifestyle changes on body composition during young adulthood.
EVALuna2:10121